The impacts of the visible differences in appearance caused by burn injuries, and medical tattooing as an appearance-based intervention - Tyerman, Catherine; Shepherd, Laura; De Boos, Danielle; Tickle, Anna (2021)
Portfolio Abstract Burns injuries can affect both adults and children. They can cause severe and enduring physical and psychological consequences, for both the individual and their family. Changes to appearance are a fundamental part of a burn injury. Medical tattooing (MT) is an intervention designed to address appearance/body dissatisfaction.